Water economization in rabi maize (Zea mays L.) to enhance productivity through land configuration and irrigation scheduling in the Indo-Gangetic Plains of India - MEENA, R. L.; IDNANI, L. K.; KUMAR, ASHOK; KHANNA, MANOJ; SHUKLA, LIVLEEN; CHOUDHARY, R. L. (Journal of Soil and Water Conservation, 2022)
A field experiment was conducted during rabi seasons (October-May) in the year 2010-11 and 2011-12 at research farm of the Indian Agricultural Research Institute, New Delhi to study the combined effects of land configuration and irrigation scheduling on productivity, profitability and water-use efficiency (WUE) of rabi maize. The treatments consisted three land configuration methods viz., L1:Flat Bed (FB); L2: Furrow Irrigated Raised Bed (FIRB) and L3: Ridge and Furrow (RF) were allocated in horizontal strip and six irrigation scheduling viz., I1: 60 mm Cumulative Pan Evaporation (CPE); I2:- 80 mm CPE; I3:- 100 mm CPE; I4:- Seedling (Sd) + Knee high (KH) + Silking (Si) + Grain filling (GF) + Dough stage (DS); I5:- Sd + Early knee high (EKH) + Late knee high (LKH) + Si + GF + DS and I6:- Sd + EKH+ KH + LKH + Si + GF + DS were allocated in vertical strip under strip plot design with three replications. The results revealed that growth (plant height, dry matter accumulation and leaf area index), yield attributes (cob/plant, cob weight/plant, grains weight/cob, grains/cob, 1000 -grain weight and shelling %), yields (grain, stover & biological yields and harvest index), economics parameters (gross return, Net return and B:C ratio) were recorded significantly highest under RF followed by FIRB and least under flat bed. The consumptive use of water was highest with FB and WUE was highest with FIRB system. Among irrigation scheduling, irrigation at 60 mm CPE enabled the crop to highest values of above mentioned growth, yield and economics parameters. However, WUE was recorded highest with 80 mm CPE. Thus, technologies of establishment of rabi maize on RF/FIRB and irrigating at either 60 or 80 mm CPE based on availability of water can be adopted to enhance the productivity of rabi maize and profitability of farmers under limited availability of irrigation water.